Fructooligosaccharides (FOS) – the hidden treasure of sugar industry - Gruska, Radosław Michał; Kunicka–Styczyńska, Alina; Baryga, Andrzej (Lodz University of Technology Press, 2025)
Fructooligosaccharides (FOS) are promising prebiotic nutrients gaining wide acceptance for their health–positive effects upon the intestinal tract, enhanced mineral absorption and metabolism regulation. Even though FOS are traditionally produced from pure sucrose or chicory roots, there is growing interest in the identification of novel sustainable and cost-effective sources. Sugar industry, represents an underused opportunity to become a major supplier of substrates for the production of FOS. Sugar factories can diversify their products while simultaneously embracing the concepts of the circular economy and reinforcing the strategies for population health by valorizing intermediate products and side–streams such as molasses, thick juice, sugar beet pulp and stored beet roots. This review summarizes the structural characteristics and health-beneficial functions of FOS and the latest advances in their enzymatic production assisted by β–fructofuranosidases and fructosyltransferases. It reveals how considered as low value sugar beet–based streams or by–products can be converted into high–value prebiotic materials through biotechnological innovation. Their industrial applications in foods, animal feeds, cosmetics and bioplastics based packaging sectors are provided with regulatory aspects and safety assessments. Looking ahead, integrated biorefinery strategies encompassing the production of FOS and the recovery of pectin and the production of ethanol and other co-products, can create novel economic and environmental possibilities for the sugar industry allowing its recognition as a diversified, health–oriented and sustainable branch beyond the traditional sucrose refining.
Keywords: fructooligosaccharides (FOS); prebiotic production; sugar industry; circular bioeconomy; functional food ingredients; fruktooligosacharydy (FOS); produkcja prebiotyków; przemysł cukrowniczy; gospodarka o obiegu zamkniętym; funkcjonalne składniki żywności